(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the processes of reforming the trade union system and the essence of effective solutions to the obstacles that are a source of it. The stages of formation and development of trade union organizations in independent Uzbekistan are revealed. Also, in the post-independence period, trade unions were formed as independent organizations from the state. These associations began to carry out their activities independently.